Misogyny in August Strindberg’s the Father - Subedi, Tika Datta (JMC Research Journal, 2023)
This paper attempts to discuss with the analysis of the play from the point of view of the author's misogynist slant disregarding other influences. Little use of social aspect will be made to the extent of its severe treatment to the protagonist by the female characters. The subversion and surrounding of the play will be studied and the particular attention will be to focus on the cause and circumstances on the misogyny whether it is associated with the theoretical perspective of naturalism or it is just the influence of the writer's biasness with females ambiance.